2022
DOI: 10.3390/ijerph19020847
|View full text |Cite
|
Sign up to set email alerts
|

External Exposure to BTEX, Internal Biomarker Response, and Health Risk Assessment of Nonoccupational Populations near a Coking Plant in Southwest China

Abstract: Benzene, toluene, ethylbenzene and xylene isomers (BTEX) have raised increasing concern due to their adverse effects on human health. In this study, a coking factory and four communities nearby were selected as the research area. Atmospheric BTEX samples were collected and determined by a preconcentrator GC–MS method. Four biomarkers in the morning urine samples of 174 participants from the communities were measured by LC–MS. The health risks of BTEX exposure via inhalation were estimated. This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A value of LCR for the pre-lockdown period was found to be similar 2.15 × 10 − 5 and 2.05 × 10 − 5 for male and female residents respectively in China, which indicated a noticeable higher carcinogenic risk for male and female residents. (Qin et al, 2022). The LCR values for all monitoring stations for benzene for pre-, during, and post lockdown periods were higher than the prescribed value (1 x 10 − 6 ), except during the lockdown period, a guideline limit value in some circumstances…”
Section: Source Identi Cation Of Vocsmentioning
confidence: 74%
“…A value of LCR for the pre-lockdown period was found to be similar 2.15 × 10 − 5 and 2.05 × 10 − 5 for male and female residents respectively in China, which indicated a noticeable higher carcinogenic risk for male and female residents. (Qin et al, 2022). The LCR values for all monitoring stations for benzene for pre-, during, and post lockdown periods were higher than the prescribed value (1 x 10 − 6 ), except during the lockdown period, a guideline limit value in some circumstances…”
Section: Source Identi Cation Of Vocsmentioning
confidence: 74%
“…The main controlling factors affecting the transport flux variations in the circulating water and sewage treatment area are ethylbenzene and o-xylene, as these pollutants have higher emissions from soil to air. Previous studies have indicated that the areas with the highest emission factors for BTEX during coal coking processes are coke ovens, coke discharging area, and sewage treatment area [58,68]. These results suggest that the coking area and sewage treatment area are key areas where BTEX are highly prone to accumulate in the soil in the steel plant.…”
Section: Distribution Characteristics Of Soil-air Btex Transport Fluxmentioning
confidence: 84%
“…The circulating water and sewage treatment area only has two components, indicating that the coking area is the region with the highest emissions of BTEX. Studies have estimated that the BTEX exposure of workers in coal loading workshops and near the coking area may be higher than that of workers in other sections [58], confirming that coking is the main pollutant-generating process and BTEX are the dominant group of pollutants emitted and retained in the coking area. for BTEX were issued in 2014 and 2022, respectively [55,56], they do not align with the monitoring requirements of this site's environmental air.…”
Section: Pollution Characteristics and Spatial Distribution Of Btex I...mentioning
confidence: 97%
“…5.69 × 10 −5 , and 4.92 × 10 −4 for MD, OKH, SON, WZ, SP, NG, and NL, respectively, in 2020; 1.06 × 10 −5 , 1.29 × 10 −5 , 1.49 × 10 −5 , 1.81 × 10 −5 , 1.98 × 10 −5 , 2.02 × 10 −5 , and 2.63 × 10 −5 for AL, WZ, NL, SON, MD, OKH, and SP, respectively, in 2021. For the pre-lockdown period, a value of LCR was established to be similar to 2.15 10 −5 and 2.05 10 −5 for male and female residents, respectively, in China, which showed discernibly higher carcinogenic risks for male and female residents [ 61 ].…”
Section: Resultsmentioning
confidence: 99%